Biochemical markers in saliva in patients with oral cancer - Anđelski-Radičević Biljana; Dožić Ivan (Serbian Medical Society - Dental Section, Belgrade, 2020)
Head and neck cancers account for 3% of all human cancers and are mainly localized in the oral cavity. Early detection of cancer is extremely important for reducing mortality and morbidity from this disease. In addition to clinical trials and histopathological findings, in the last two decades, with technological development, more specific and sensitive methods have been used in the analysis of salivary markers. The aim of this study was to present a wide range of analyzed markers in saliva: different protein markers (total proteins , albumin, defensins, staterin, cystatins), epithelial and molecular markers (CA125, CA19-9, TPA, CEA, CYFRA 21-1, CD44), enzymes (LDH, ALP, MMP, SOD), cytokines (IL-6, IL-8, IL-1b, TNF-a), oxidative stress markers (8-OHdG, MDA), non-enzymatic antioxidants (glutathione, uric acid, albumin, vitamin C and E) etc. Collecting saliva is simple and painless for the patient, it does not require expensive equipment or specially trained staff, and it is possible to take saliva several times and in unlimited quantities. Extensive research that is increasingly being done with modern techniques indicates that saliva may be useful for early detection of the disease in the near future.